Perbandingan Produktivitas, Biaya Pokok Produksi Dan Pendapatan Usahatani Padi Organik Dan Nonorganik Di Kabupaten Pringsewu - Sari Nurhidayati; Agus Hudoyo; Dwi Haryono (Journal of Food System & Agribusiness, 2021)
Pringsewu Regency has the highest organic rice production area in Lampung Province, but organic rice productivity is low. Farmers have not fully carried out organic rice farming, most farmers are farming nonorganic rice. This is because farmers think that low productivity causes the income of rice farmers decreased. This study aims to analyze the differences in productivity, costs, and income of organic and nonorganic rice farming in Pringsewu Regency. Data were collected in two sub-districts which are organic and nonorganic rice farmers in Pringsewu District, namely: Pringsewu and Pardasuka districts, in August 2020. The number of respondents was 18 people by observing the last 3 planting seasons namely MH 2019/2020, MK 2019 and MH 218/2019. Therefore the total observations were 108. The data were analyzed using multiple regression analysis models with the dependent variable, namely productivity, costs and income. The independent variables are organic rice, location and planting season. The results showed that the average productivity of organic rice farming was 0.97ton/ha lower than that of nonorganic rice. The average cost of organic rice farming was Rp. 1.593/kg higher than nonorganic rice. The average income of organic rice farming was Rp. 7,13 milion/ha higher than nonorganic rice.